2013
DOI: 10.1021/jf305067n
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Monascin on Anti-inflammation Mediated by Nrf2 Activation in Advanced Glycation End Product-Treated THP-1 Monocytes and Methylglyoxal-Treated Wistar Rats

Abstract: Hyperglycemia is associated with advanced glycation end products (AGEs). This study was designed to evaluate the inhibitory effects of monascin on receptor for advanced glycation end product (RAGE) signal and THP-1 monocyte inflammation after treatment with S100b, a specific ligand of RAGE. Monascin inhibited cytokine production by S100b-treated THP-1 monocytes via up-regulation of nuclear factor-erythroid 2-related factor-2 (Nrf2) and alleviated p47phox translocation to the membrane. Methylglyoxal (MG, 600 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 47 publications
(104 reference statements)
2
45
0
Order By: Relevance
“…These antioxidant and antiglycation properties may explain the efficacy of retinoic acid against MG toxicity on brain endothelial cells according to real-time viability assay. The beneficial effect of retinoic acid was also reported in MG-induced diabetes in rats (63). In the present study retinoic acid preserved the integrity of the endothelial barrier from the permeability increasing effect of MG.…”
Section: Protection Against Methylglyoxal-induced Injury In Brain Endsupporting
confidence: 84%
“…These antioxidant and antiglycation properties may explain the efficacy of retinoic acid against MG toxicity on brain endothelial cells according to real-time viability assay. The beneficial effect of retinoic acid was also reported in MG-induced diabetes in rats (63). In the present study retinoic acid preserved the integrity of the endothelial barrier from the permeability increasing effect of MG.…”
Section: Protection Against Methylglyoxal-induced Injury In Brain Endsupporting
confidence: 84%
“…In agreement with these previous studies, our study indicated that resveratrol can at least partially activate the ERK signaling pathway, which was previously shown to enhance Nrf2 nuclear translocation and activation [ 39 ]. In addition, activation of Nrf2 by several compounds, including monascin, ankaflavin and dimerumic acid, elevated MG metabolism to alleviate diabetic damage in vivo [ 53 , 54 , 55 , 56 ]. Activation of Nrf2 also protected from oxidation of high-density lipoprotein cholesterol [ 57 ] and airway inflammation in vivo [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…NAC is a clinically approved drug with antioxidant properties, which is known as an MG scavenger and inhibitor of ROS formation both in vitro and in vivo . Monascin, a novel product derived from the mold gender Monascus with potential antidiabetic properties, was recently identified as an agonist of both Nrf2 and PPARγ, having protective effects on MG‐induced toxicity, anti‐inflammatory properties in MG‐treated monocytes and protecting effects in MG‐treated β‐cells . However, more studies are necessary to evaluate its therapeutic potential.…”
Section: The Promise Of New Therapeutic Targetsmentioning
confidence: 99%